Faktor-faktor yang Mempengaruhi Organizational Citizenship Behavior serta Pengaruhnya Terhadap Kinerja Guru Sekolah Dasar Di Wilayah Perairan Kabupaten Banyuasin - Maryani Maryani; Trisniarty Adjeng Moelyati; Mustofa Marlibatubara (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aimed to determine the factors that affect organizational citizenship behavior (OCB) and its influence on teacher performance Elementary School (SD) in the territorial waters of Banyuasin. The data of this study using cross section data. The variables are expressed in this research teacher performance, organizational citizenship behavior (OCB), motivation, organizational commitment, job satisfaction. The population in this study sample of 1,140 teachers and 270 teachers in this study. The sampling technique using cluster sampling and analysis techniques using Structural Equation Modelling (SEM) with AMOS program assistance. The results showed that motivation to work but not significant positive effect on OCB, organizational commitment and significant positive effect on OCB, job satisfaction and no significant negative effect on OCB, job motivation positive and significant impact on performance, organizational commitment significantly influence performance, job satisfaction and no significant negative effect on performance, OCB positive and significant effect on performance.The study reveals that the potential of existing OCB can significantly improve the performance of teachers. Education managers should be able to maximize the potential of OCB that has been owned.